Doing Business Economy Profile 2012 : Timor-Leste - World Bank; International Finance Corporation (Washington, DC, 2017)
Doing business sheds light on how easy or difficult it is for a local entrepreneur to open and run a small to medium-size business when complying with relevant regulations. It measures and tracks changes in regulations affecting 10 areas in the life cycle of a business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts and resolving insolvency. In a series of annual reports doing business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 183 economies, from Afghanistan to Zimbabwe, over time. This economy profile presents the doing business indicators for Timor-Leste. To allow useful comparison, it also provides data for other selected economies (comparator economies) for each indicator. The data in this report are current as of June 1, 2011 (except for the paying taxes indicators, which cover the period January-December 2010).